Catching The Vision: Guidance And Counselling In Nova Scotia’s Schools - Sumarah, John; Lehr, Ron (Canadian Journal of Counselling and Psychotherapy, 2007)
A province-wide evaluation of the new Comprehensive Guidance and Counselling Program undertaken in Nova Scotia provides strong support for a "program-based model" of counselling. More than 90% of the 46 school counsellors involved in the implementation of the Program responded to a survey regarding the various program components, advisory groups, needs assessment, resources, outcomes, evaluation, and roles of educational partners. Focus groups, representing all school districts, provided qualitative data related to counsellors' overall impressions of the Program, what was working, concerns, and professional needs. Evaluation results addressed questions related to the appropriateness, adequacy, efficiency, and effectiveness of the Program.